2006
DOI: 10.1128/iai.74.1.108-117.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Brucella suis Type IV Secretion System Assembles in the Cell Envelope of the Heterologous Host Agrobacterium tumefaciens and Increases IncQ Plasmid pLS1 Recipient Competence

Abstract: Pathogenic Brucella species replicate within mammalian cells, and their type IV secretion system is essential for intracellular survival and replication. The options for biochemical studies on the Brucella secretion system are limited due to the rigidity of the cells and biosafety concerns, which preclude large-scale cell culture and fractionation. To overcome these problems, we heterologously expressed the Brucella suis virB operon in the closely related ␣ 2 -proteobacterium Agrobacterium tumefaciens and show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Apart from the in vitro assays for VirB protein interactions, one of the main advances of our recent work was the development of a heterologous assay of B. suis T4SS assembly in A. tumefaciens (29). This assay exploits the ability of a subset of B. suis T4SS components (VirB1 and VirB3-VirB12) to increase the recipient competence of A. tumefaciens for T4SS-mediated plasmid transfer, and similar findings were reported for the Agrobacterium VirB T4SS (30).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Apart from the in vitro assays for VirB protein interactions, one of the main advances of our recent work was the development of a heterologous assay of B. suis T4SS assembly in A. tumefaciens (29). This assay exploits the ability of a subset of B. suis T4SS components (VirB1 and VirB3-VirB12) to increase the recipient competence of A. tumefaciens for T4SS-mediated plasmid transfer, and similar findings were reported for the Agrobacterium VirB T4SS (30).…”
Section: Discussionmentioning
confidence: 64%
“…Escherichia coli strains JM109 (32) and GJ1158 (33) were used as hosts for cloning and protein overproduction, respectively. A. tumefaciens strain A348 was used as pLS1 donor and strain UIA143 as host for the heterologous expression of the B. suis T4SS, plasmid propagation, and cell cultivation, which were conducted as described (29). For detection of VirBs protein production, B. suis strains were cultivated in minimal medium (34), and J774 murine macrophage-like cells were infected with a standard gentamicin protection assay (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, the VirB Bs proteins also stimulate DNA uptake when synthesized in agrobacterial recipient cells. Although the underlying mechanism for enhanced DNA uptake is unknown, this assay enables further structure-function studies of the Brucella VirB machinery in the A. tumefaciens surrogate host (45). Additionally, although most Brucella subunits are not interchangeable with homologs of other T4SS, VirB1 Bs functionally substitutes for VirB1 At (133).…”
Section: More Gram-negative Systemsmentioning
confidence: 99%
“…We have previously shown that VirB proteins are expressed at a very low level by B. suis in rich or minimal medium at neutral pH, whereas transcription of the B. suis virB operon is strongly induced in acid minimal medium, conditions thought to mimic the environment encountered in the phago-some (2, 13). We used Western blotting with antibodies raised against recombinant B. suis VirB5, VirB8, VirB9, VirB10, and VirB12 to compare expression of these proteins by wild-type B. suis and the BS1008 mutant cultured in virB operon-inducing medium at either pH 7.0 or pH 4.5 as described previously (3,14). Low-level expression of the five VirB proteins was detected in wild-type B. suis after incubation at neutral pH, and very strong induction was observed in acid minimal medium (Fig.…”
mentioning
confidence: 99%